2015
DOI: 10.2147/amep.s78441
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of doctors' performance as facilitators in basic medical science lecture classes in a new Malaysian medical school

Abstract: BackgroundDidactic lecture is the oldest and most commonly used method of teaching. In addition, it is considered one of the most efficient ways to disseminate theories, ideas, and facts. Many critics feel that lectures are an obsolete method to use when students need to perform hands-on activities, which is an everyday need in the study of medicine. This study evaluates students’ perceptions regarding lecture quality in a new medical school.MethodsThis was a cross-sectional study conducted of the medical stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…About 72% of study respondents were sure that HSNZ had antibiotic guidelines, but 50% of them did not possess a copy of the guide, and only 45% had consulted the antibiotic guidelines ( Figure 1 ). Study findings showed that the respondents have realized there is a gap between their theoretical lecture-based input, 72 regarding antimicrobials, and clinical practice. Similar studies from different countries also indicated demand for more educational intervention.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…About 72% of study respondents were sure that HSNZ had antibiotic guidelines, but 50% of them did not possess a copy of the guide, and only 45% had consulted the antibiotic guidelines ( Figure 1 ). Study findings showed that the respondents have realized there is a gap between their theoretical lecture-based input, 72 regarding antimicrobials, and clinical practice. Similar studies from different countries also indicated demand for more educational intervention.…”
Section: Discussionmentioning
confidence: 96%
“… 71 As other universities in Malaysia, UniSZA is subscribed to the integrated curriculum for undergraduate medical education and pharmacology is taught in preclinical years of Year I and II as a lecture-based subject. 72 The Faculty of Medicine, UniSZA, is scheduled to conduct a major revision in the next few years of the undergraduate medical curriculum. 73 , 74 Therefore, this exercise is to ensure highly professional and committed medical doctors are produced in society.…”
Section: Introductionmentioning
confidence: 99%